An algorithm for the compensation of short-period errors in optical encoders. (24th September 2015) - Mendenhall, Marcus H; Windover, Donald; Henins, Albert; Cline, James P
Abstract: We present a simple way to collect data from an optical position-or-angle encoder with a readout that interpolates values between the optical features, and to process these data to determine the short-range errors that arise from an interpolation process. This is commonly known as generating the compensation function for such an encoder. This process allows the user of data from an encoder to make this correction without relying on undocumented internal algorithms which may be provided by the encoder manufacturer. It can also be used to test built-in algorithms by measuring the residual error when internal algorithms are used. We apply the algorithm to a commercial angular encoder, installed in a goniometer, as an example. The determination of this function on an encoder is critical to provable angle or position metrology efforts.